Putting women at the center: a review of Indian policy to address person-centered care in maternal and newborn health, family planning and abortion - Aradhana Srivastava; Devaki Singh; Dominic Montagu; Sanghita Bhattacharyya (BMC, 2017)
Abstract Background Person-centered care is a critical component of quality care, essential to enable treatment adherence, and maximize health outcomes. Improving the quality of health services is a key strategy to achieve the new global target of zero preventable maternal deaths by 2030. Recognizing this, the Government of India has in the last decade initiated a number of strategies to address quality of care in health and family welfare services. Methods We conducted a policy review of quality improvement strategies in India from 2005 to 15, covering three critical areas- maternal and newborn health, family planning, and abortion (MNHFP + A). Based on Walt and Gilson's policy triangle framework, we analyzed the extent to which policies incorporated person-centered care, while identifying unaddressed issues. Data was sourced from Government of India websites, scientific and grey literature databases. Results Twenty-two national policy documents, comprising two policy statements and 20 implementation guidelines of specific schemes were included in the review. Quality improvement strategies span infrastructure, commodities, human resources, competencies, and accountability that are driving quality assurance in MNHFP + A services. However, several implementation challenges have affected compliance with person-centered care, thereby affecting utilization and outcomes. Conclusion Focus on person-centered care in Indian MNHFP + A policy has increased in recent years. Nevertheless, some aspects must still be strengthened, such as positive interpersonal behavior, information sharing and promptness of care. Implementation can be improved through better provider training, patient feedback and monitoring mechanisms. Moreover, unless persisting structural challenges are addressed implementation of person-centered care in facilities will not be effective.